Implementasi pendidikan agama Kristen yang relevan dalam masyarakat majemuk sebagai dimensi misi gereja - Tarrapa, Setrianto (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
The reality of pluralism in the context of Indonesia on the one hand, is a challenge towards the implementation of Christian Religious Education. However, on the other hand, Christian Religious Education is becoming very essential for Christians to demonstrate the love of God in the midst of society. Christians are always in touch with adherents of other religions, even that kind of relationship feels so strong in various areas of life. This problem triggers how the idea of implementing Christian Education is relevant in the pluralistic context in Indonesia. This study was analyzed using qualitative research methods through library research techniques. Findings showed that, in the pluralistic context, the implementation of Christian Religious Education in Indonesia as an integral part of the mission can be carried out through three aspects, namely: revitalizing the thinking paradigm about pluralism; interpreting the implementation strategy of Christian Religious Education in a pluralistic society and mainstreaming and building the vision and mission of multicultural based Christian Religious Education. AbstrakRealitas kemajemukan dalam konteks Indonesia di satu sisi merupakan tanatangan terhadap pelaksanaan pendidikan agama Kristen, namun di sisi lain Pendidikan agama Kristen menjadi amat penting bagi orang Kristen untuk mendemonstrasikan kasih Allah di tengah-tengah masyarakat. Orang orang Kristen selalu bersentuhan dengan penganut agama lain, bahkan sentuhan itu terasa amat kuat dalam berbagai bidang kehidupan. Permasalahan ini memicu bagaimana gagasan pelaksanaan Pendidikan Kristen yang relevan dalam konteks majemuk di Indonesia. Kajian ini ditelaah dengan menggunakan metode penelitian kualitatif melalui teknik pustaka. Hasil temuan menunjukkan bahwa dalam konteks majemuk penyelenggaraan Pendidikan agama Kristen di Indonesia sebagai bagian integral misi dapat dilakukan melalui tiga aspek yaitu: merevitalisasi paradigma berpikir tentang kemajemukan; mereinterpretasi strategi pelaksanaan Pendidikan agama Kristen dalam masyarakat yang majemuk; serta mengarusutamakan dan membangun visi dan misi pendidikan agama Kristen berbasis multikultural